2022
DOI: 10.1007/s40615-022-01294-7
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Prevention and Care of COVID-19 Infection in Cincinnati Latinx Families: a Community-Based Convergent Mixed Methods Study

Abstract: Background Latinx populations have experienced disproportionately high case rates of COVID-19 across the USA. Latinx communities in non-traditional migration areas may experience greater baseline day-to-day challenges such as a lack of resources for immigrants and insufficient language services. These challenges may be exacerbated by the COVID-19 pandemic. Objective This article describes the results of an initial community health needs assessment to better understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…( Table 2 ). Thirty-five studies mainly or totally used the term “food insecurity” [ 26 , 27 , 28 , 29 , 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], six used “food security” [ 25 , 30 , 32 , 63 , 64 , 65 ], and five used both [ 66 , 67 , 68 , 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…( Table 2 ). Thirty-five studies mainly or totally used the term “food insecurity” [ 26 , 27 , 28 , 29 , 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], six used “food security” [ 25 , 30 , 32 , 63 , 64 , 65 ], and five used both [ 66 , 67 , 68 , 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the 46 studies included in this scoping review [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ], half of them were conducted in America [ 28 , 29 , 31 , 33 , 40 , 42 , 43 , 46 , 47 , 48 , 49 , 50 <...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review evaluating the factors contributing to COVID-19 disparities across ethnic groups found that the primary drivers were differences in health care access and exposure risk, such as household crowding and population density [ 32 ]. Among Latinx people, various studies found that the main drivers were employment, housing, and immigration-related insecurity [ 29 , 30 , 33 ].…”
Section: Empirical Foundationmentioning
confidence: 99%